A medical doctor examines life on three continents : a Pakistani view - Ehtisham, S. Akhtar, 1939- (Algora Pub., 2008)
A medical doctor and political activist traces his life from India at partition to graduate work and practice in the UK and America, comparing health standards, economic well-being, race relations, and the political atmosphere on three continents during the socially-conscious 1960s and later under bare-knuckle capitalism. He includes a brief synopsis of Pakistan?s tumultuous history, including the role played by superpowers with an interest in the region.